Geographical distribution of health indicators related to snake bites and envenomation in Morocco between 1999 and 2013 - El hattimy, Faiçal (Epidemiol Health, 2018)
OBJECTIVES: Envenomation from snake bites is a significant cause of morbidity and mortality worldwide. The aim of this study was to describe the epidemiological features of snake bites in Morocco and to evaluate time-space trends in snake bite incidence, the mortality rate, and the case-fatality rate. METHODS: This is a retrospective study of snake bite cases reported to the Moroccan Poison Control Center between 1999 and 2013. RESULTS: During the study period, 2,053 people were bitten by snakes in Morocco. Most victims were adults (55.4%). The average age of the patients was 26.48±17.25 years. More than half of the cases (58.1%) were males. Approximately 75% of snake bites happened in rural areas, and 85 deaths were recorded during this period. The incidence of snake bites remained generally steady over the 15-year period of this study, with a marked increase noted since 2012. The mortality rate has increased slightly, from 0.02 deaths per 100,000 inhabitants in 1999 to 0.05 in 2013. The geographical distribution of snake bite cases in the regions of Morocco showed that Tanger-Tétouan had the highest annual incidence of snake bites (1.41 bites per 100,000 inhabitants). However, the highest annual mortality rates were recorded in the Guelmim-Es Semara and Souss-Massa-Drâa regions (0.09 deaths per 100,000 inhabitants for both regions). CONCLUSIONS: The geographical distribution of the incidence, mortality, and case-fatality rates of snake bites in Morocco showed large disparities across regions during the three 5-year periods included in this study, meaning that certain areas can be considered high-risk for snake bites.